Raising Awareness of Expressive Writing as a Method for Alleviating the Trauma of Hurricane Dorian in The Bahamas - Furst , Saskia; Hellberg, Dustin C (International Journal of Bahamian Studies, 2023)
To date, there has been no published research on the use of expressive writing therapy in The Bahamas. However, studies within the fields of clinical psychology and psychiatric medicine have explored both the emotional and physical benefits of expressive writing therapy in dealing with various types of trauma. In the aftermath of Hurricane Dorian, expressive writing workshops were conducted at the University of The Bahamas in an ad hoc manner to potentially assist in reducing the trauma experienced by students. This paper will explore the potential for future, long-term studies as well as the potential need to raise greater awareness and appreciation for this method of reducing the negative mental and physical health impacts of traumatic natural disasters on the emotional well-being of Bahamians and residents. Results could also potentially be applicable to other Small Island Developing States.